SOCIAL AND ECONOMIC CONSEQUENCES OF SPATIAL ASYMMETRY IN POULTRY MARKETS AT THE REGIONAL LEVEL - ULYCH, Volodymyr; YAZLYUK, Borys; TSIUPAK, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article studies the socioeconomic aspects of spatial asymmetry in poultry markets at the regional level. It aims to analyze the theoretical and methodological foundations for ensuring regions’ socioeconomic development and investigate the impact of spatial asymmetries in poultry markets on this development. The study shows that the socioeconomic development of regions is an objective process of systemic and positively directed changes that encompass socioeconomic, organizational, and technical economic parameters of regional functioning. These changes contribute to the improvement of the population’s level and quality of life. The socioeconomic development of regions involves several key components, including production and income growth, transformations in institutional and social structures, infrastructure improvements, changes in public consciousness, environmental sustainability, and support for small and medium-sized enterprises. The research on poultry production volumes and the number of poultry enterprises across country regions revealed significant disparities in the development levels of different areas. A significant portion of poultry enterprises was concentrated in specific regions, creating an imbalance in the distribution of economic resources between territories. The study identifies regional spatial asymmetry in the poultry market as the result of the interaction of numerous factors, including natural conditions, infrastructure, investment attractiveness, human potential, government support, demand for products, and technological development of the industry. These factors determine the concentration of production capacities in specific regions and contribute to the uneven development of poultry farming across the country. The article justifies the impact of poultry enterprise concentration on the socioeconomic development of regions with varying levels of this concentration. Increased production volumes, higher employment levels, more significant tax revenues for local budgets, and improved living standards for the population characterize regions with a high concentration of poultry enterprises. However, these regions also face challenges related to high levels of environmental pollution, requiring ecological rehabilitation measures. In contrast, regions with low poultry concentration have limited opportunities for business development and low employment rates, leading to increased migration and decreased purchasing power of the population. These regions also face difficulties financing social projects and attracting investments, complicating sustainable development. At the same time, these regions exhibit lower environmental pollution and a more stable population structure.